(untitled) (CIPEEX, 2025)
Introduction: Complaints related to vaginal infections account for 40% of gynecological consultations and are characterized by leukorrhea, itching, burning sensation, and foul odor. These pathologies have behavioral aspects as their main risk factors. Therefore, it is essential to continuously improve the quality of epidemiological information. Objective: to conduct a survey of data on the prevalence of these infections through studies published in the thesis and dissertation databases of the Federal University of Goiás (UFG), Pontifical Catholic University of Goiás (PUC-Goiás), and University of Brasília (UnB). Methodology: This is an integrative literature review, with studies searched on the institutional thesis and dissertation databases of the UFG, PUC-Goiás, and UnB universities. A total of nine studies were selected. Results: Vulvovaginal candidiasis had discharge, itching, and burning as the main symptoms reported. Bacterial vaginosis had the highest prevalence and was associated with abnormal vaginal discharge, which was statistically significant for diagnosis, as well as with the use of vaginal douching. Condom use was a protective factor against trichomoniasis, and PCR was the most specific diagnostic method. Cervicitis was associated with non-use or irregular use of condoms and had a lower prevalence. Conclusion: Suggestive clinical findings are the main indicators of etiology, and behavioral and sociodemographic aspects did not show significant differences for most causes of vaginal discharge.